Healthcare Resource Utilization Associated with Leukopenia and Neutropenia in Kidney Transplant Recipients Receiving Valganciclovir in the United States - Qinghua Li; Vladimir Turzhitsky; Pamela Moise; Harry Jin; Kaylen Brzozowski; Irina Kolobova (Journal of Health Economics and Outcomes Research)
**Background:** Cytomegalovirus prophylaxis in kidney transplant recipients (KTRs) is limited by post-transplant neutropenia and leukopenia (PTN/PTL). Despite its clinical significance, the healthcare resource utilization (HCRU) related to PTN/PTL remains poorly characterized. **Objective:** To evaluate HCRU among KTRs taking valganciclovir during their first year post-transplant. **Methods:** Using TriNetX Dataworks-USA, a federated, de-identified electronic medical record database, we identified adult KTRs who underwent their first kidney transplant from January 2012 to September 2020. All eligible patients were followed for 1 year. PTN/PTL was defined as absolute neutrophil count less than 1000/μL or white blood cell count less than 3500/μL. Multivariable logistic/Poisson regression models were used to assess the association between PTN/PTL and various HCRU types. **Results:** A total of 8791 KTRs were identified, of whom 6219 (70.7%) developed PTN/PTL at a mean of 5.7 months post-transplantation. Hospitalizations, rehospitalizations, emergency room visits, outpatient appointments, packed red blood cell transfusions, and granulocyte-colony stimulating factor administration were more prevalent among KTRs with PTN/PTL (61.1% vs 49.5%, 24.5% vs 14.1%, 35.2% vs 28.9%, 30.4 vs 26.2 visits, 22.3% vs 17.6%, 23.4% vs 2.2%, respectively; P < .001). Adjusted analyses confirmed that PTN/PTL correlated with increased HCRU across all categories. **Conclusions:** KTRs who developed PTN/PTL had significantly higher HCRU. Further studies are needed to evaluate strategies addressing PTN/PTL for KTRs.